COLLABORATION BETWEEN REGULATORS AND THE COMMUNITY IN LAND ECONOMIC REFORM: A POLICY STUDY BASED ON REAL NEEDS - Yustinus Lambang Setyo Putro; Siti Nur Azizah; Gunawan Widjaja; Dyah Ersita Yustanti (Adisam Publisher, 2025)
This study discusses collaboration between regulators and the community in the context of land economic reform using a real needs-based policy approach. The emergence of various agrarian conflicts in Indonesia shows that top-down land policies tend to be ineffective because they do not pay sufficient attention to the aspirations and real needs of the community. Through a literature review, this study examines the dynamics of the regulator-community relationship, identifies factors contributing to the success and obstacles to collaboration, and emphasises the urgency of active community participation in policy formulation. The results of the discussion show that collaboration not only strengthens the legitimacy of policies but also creates solutions that are more inclusive, transparent, and adaptive to social realities. In addition, policies based on real needs have proven to be more conducive to achieving certainty of rights, fair land redistribution, and the strengthening of agrarian justice. Thus, the integration of collaboration and a real needs approach is an important foundation for promoting sustainable land economic reform in Indonesia.